Antioxidant Activities of n-Hexane Soluble and Insoluble Fraction, Ethyl Acetate Soluble and Insoluble Fraction from Ethanol Extract of Sambung Nyawa Leaf (Gynura procumbens (Lour.) Merr.) - Purwantiningsih Purwantiningsih; Retno Murwanti; Lukman Hakim (Majalah Obat Tradisional, 2019)
There were many plants containing flavonoids which can function as antioxidant. Antioxidant can be used to decrease the mortality rate caused by degenerative and infectious diseases. This study aims to determine the antioxidant potency of n-hexane soluble and insoluble fraction, ethyl acetate soluble and insoluble fraction, and the ethanol extract antioxidant activity of Sambung Nyawa leaf (Gynura procumbens (Lour.) Merr.). The ethanol extract of G. procumbens leaves was obtained by maceration using 70% ethanol then fractionated using hexane and ethyl acetate to obtain the n-hexane soluble fraction, n-hexane insoluble fraction, ethyl acetate soluble fraction, and ethyl acetate insoluble fraction. The antioxidant activity study of ethanol extract, n-hexane soluble, and insoluble fraction, ethyl acetate soluble, and insoluble fraction of G. procumbens was carried out using DPPH (2,2- diphenyl-1-picrylhydrazyl) method to evaluate its free radical scavenging activity with a comparison of vitamin C. The antioxidants activity was expressed as IC50 value. The IC50 value for vitamin C and ethanol extract of G. procumbens leaves were 2.41 µg/ml and 200 µg/ml. On the other hand, the n-hexane soluble and insoluble fraction had an IC50 value of 78 µg/ml and 34 µg/ml, while ethyl acetate soluble and insoluble fraction had the potency as an antioxidant with an IC50 value of 419 µg/ml and 151 μg/ml, respectively. Based on the results obtained, the antioxidant potency of G. procumbens ethanol extract and their fraction were successively of n-hexane insoluble fraction > n-hexane soluble fraction > ethyl acetate insoluble fraction > ethanol extract > ethyl acetate soluble fraction.